Dampak Tren Global Terhadap Pariwisata Dan Bisnis Kreatif di Provinsi Lampung - Selfia Alke Mega (LPPM Universitas HKBP Nommensen, 2025)
Lampung Province, with its natural beauty and cultural richness, has great potential for developing tourism and creative businesses. However, global trends such as increased tourist visits, diversification of tourism products, the role of digital tourism ambassadors, local economic growth, and environmental awareness have brought significant changes to this industry. This study aims to analyze the impact of global trends such as increased tourist visits, diversification of tourism products, the role of digital tourism ambassadors, local economic growth, and environmental awareness on tourism and creative industries in Lampung Province. A literature review method was used to collect data from various relevant sources, such as scientific articles, research reports, and statistical data. The results of the study indicate that global trends have a significant impact on tourism and creative industries in Lampung Province. The increase in tourist visits has driven the diversification of tourism products, such as nature tourism, cultural tourism, and culinary tourism. The role of digital tourism ambassadors is crucial in promoting Lampung on social media platforms and attracting new tourists.